2021
DOI: 10.1038/s41598-021-92420-8
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial cell changes and surgical results after Ahmed glaucoma valve implantation: ciliary sulcus versus anterior chamber tube placement

Abstract: We compared the changes in corneal endothelial cells and surgical outcomes after Ahmed glaucoma valve (AGV) implantation with the valve tip inserted either into ciliary sulcus (CS) or anterior chamber (AC). We retrospectively reviewed the medical records of patients treated with CS AGV (n = 24) and AC AGV (n = 38). We compared the preoperative and postoperative central corneal endothelial cell density (ECD), endothelial cell coefficient of variation (CV), best-corrected visual acuity, intraocular pressure (IOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…Based on previous reports that suggested a graft failure of 8∼26% with AGV implantation at 12 months in patients with penetrating keratoplasty (2,(20)(21)(22), our data showed a graft failure of 33% with AGV implantation, which were comparable with previous reports. The mean loss of ECD was 653/mm 2 /year in the AGV, which was comparable with previous reports (−315 cells/mm 2 /year) (21) and a recent study has suggested ECD loss of −519.97 cells/mm 2 for 2 years (23). Given that the patients who showed unacceptably high IOP based on their severity or progression of the optic nerve damages or visual field defects had undergone AGV implantation, high pre-operative IOP in AGV, although it was insignificant, may also affect changes of ECD.…”
Section: Discussionsupporting
confidence: 91%
“…Based on previous reports that suggested a graft failure of 8∼26% with AGV implantation at 12 months in patients with penetrating keratoplasty (2,(20)(21)(22), our data showed a graft failure of 33% with AGV implantation, which were comparable with previous reports. The mean loss of ECD was 653/mm 2 /year in the AGV, which was comparable with previous reports (−315 cells/mm 2 /year) (21) and a recent study has suggested ECD loss of −519.97 cells/mm 2 for 2 years (23). Given that the patients who showed unacceptably high IOP based on their severity or progression of the optic nerve damages or visual field defects had undergone AGV implantation, high pre-operative IOP in AGV, although it was insignificant, may also affect changes of ECD.…”
Section: Discussionsupporting
confidence: 91%
“…However, the percentage of postoperative ECD loss was lower in the gAGV group, and the rate of ECD change was also lower in the gAGV group, which implied that less corneal endothelial damage occurred in the gAGV group within 2 years after surgery. The rate of ECD change with guided AGV implantation in our study appeared to be comparable to the rate of ECD change with tube insertion in the CS in previous studies (-0.36%/month in Kim et al 27 and − 0.72%/month in Zhang et al 28 ). However, the overall degrees and rates of ECD change in this study were relatively higher than those reported previously.…”
Section: Discussionsupporting
confidence: 89%
“…AGV tube insertion into the CS using the iris as a mechanical barrier has signi cantly lower rates of ECD change than tube insertion in the AC in previous studies. [26][27][28] However, tube implantation in the CS may be related to a higher incidence of postoperative hemorrhage, since the CS shows greater vascularization than the AC, 29 as well as intraocular lens (IOL)-related complications and capsular bag stability and zonular weakness should also be considered, and the structural di culty of tube insertion in the CS may be present in Asian eyes with relatively small axial lengths. Placing the tube on the par plana can minimize the effect of the tube on the corneal endothelium but is limited by the prerequisite that previous vitrectomy must be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Implant positioning and its proximity to the corneal endothelial layer is a key factor for tube-associated CEC loss [43,44]. In a retrospective study of 62 eyes, anterior chamber Ahmed glaucoma valves resulted in significantly higher CEC loss after 36 months as compared with ciliary sulcus implantation (25.6 vs. 7.1%) [19]. Another cohort study also noted significantly higher CEC loss associated with anterior chamber Baerveldt tubes as compared with pars plana tubes after 12 months (12.1% vs. no significant loss) [18].…”
Section: Discussionmentioning
confidence: 99%